2017
DOI: 10.1177/2192568216687546
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cervical Infection: Presentation and Incidence of an Uncommon Postoperative Complication

Abstract: Study Design:Retrospective multi-institutional case series.Objective:The anterior cervical discectomy and fusion (ACDF) affords the surgeon the flexibility to treat a variety of cervical pathologies, with the majority being for degenerative and traumatic indications. Limited data in the literature describe the presentation and true incidence of postoperative surgical site infections.Methods:A retrospective multicenter case series study was conducted involving 21 high-volume surgical centers from the AOSpine No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
1
17
1
Order By: Relevance
“…The revision rate for surgical site infection following anterior spinal surgery in the present series was 0.34%, comparable to international reports of rates between 0.07% and 1.6% [7][8][9].…”
Section: Comparison With the Literaturesupporting
confidence: 86%
See 1 more Smart Citation
“…The revision rate for surgical site infection following anterior spinal surgery in the present series was 0.34%, comparable to international reports of rates between 0.07% and 1.6% [7][8][9].…”
Section: Comparison With the Literaturesupporting
confidence: 86%
“…Ghobrial et al [9], in a retrospective series, reported 6 septic complications in 8887 cases in 21 US centers, for a mean septic complication rate of 0.07% (range: 0-0.39%). Fountas et al [7], in a retrospective series of 1015 patients, reported a single early abscess (0.15%), as did Bertalanffy and Eggert [10] in a series of 450 patients (i.e., 0.2%).…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…Infections following ACDF are rare and require reoperation to address the infection. 20 Infection increases inflammation and difficulty of the operation; therefore, the possible increased risk of recurrent laryngeal nerve injury is not surprising. The association of C7/T1 with increased risk of injury is also not surprising given the anatomical course of the recurrent laryngeal nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Finiels using the same implant in 61 patients reported any complication of this type[23] and this, notwithstanding the mean rate of infection is of 0.07%–1.6% in the medical literature. [25262728] Fusion rate is an important criterion for a good outcome. It varies from 71.4% to 92.1% for single-disc implant without instrumentation.…”
Section: Discussionmentioning
confidence: 99%